2016
DOI: 10.1212/nxi.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of spontaneous EAE by laquinimod reduces Tfh, B cell aggregates, and disease progression

Abstract: Objective:To evaluate the influence of oral laquinimod, a candidate multiple sclerosis (MS) treatment, on induction of T follicular helper cells, development of meningeal B cell aggregates, and clinical disease in a spontaneous B cell–dependent MS model.Methods:Experimental autoimmune encephalomyelitis (EAE) was induced in C57BL/6 mice by immunization with recombinant myelin oligodendrocyte glycoprotein (rMOG) protein. Spontaneous EAE was evaluated in C57BL/6 MOG p35-55–specific T cell receptor transgenic (2D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…correlated with reduced TFH frequency and B-cell aggregates in the CNS88 . This work suggests that TFH cells are linked with disease progression.…”
mentioning
confidence: 87%
“…correlated with reduced TFH frequency and B-cell aggregates in the CNS88 . This work suggests that TFH cells are linked with disease progression.…”
mentioning
confidence: 87%
“…Similar to human studies, many of the studies in mice examining TFH cells are simply looking at correlative data. For example, one study reported that Laquinomod effectively treated human MOG-induced and the efficacy was correlated with reduced TFH frequency and B-cell aggregates in the CNS [ 99 ]. This work suggests that TFH cells are linked with disease progression.…”
Section: Experimental Autoimmune Encephalomyelitis (Eae)mentioning
confidence: 99%
“…Preclinical studies have shown that laquinimod reduces inflammatory cell infiltrates in the central nervous system (CNS), inhibits development of experimental autoimmune encephalomyelitis, decreases demyelination, and prevents axonal loss [ 7 , 8 ], and the formation of meningeal B cell aggregates [ 9 ]. Laquinimod is likely to exert its anti-inflammatory activity via suppression of Th1 and Th17 cells and induction of a Th2/3 shift of immune response in the peripheral blood [ 7 13 ].…”
Section: Introductionmentioning
confidence: 99%